Aesthetic outcome of the face after 2-stage palate repair for complete unilateral cleft lip and palate - Feitosa, Leonardo Bezerra (2022)
Cleft lip and palate repair aims to rebuild the function of orofacial structures, decreasing the impact on language development, masticatory function and airways, as well as creating a harmonic, symmetrical nasolabial appearance with minimal scarring. There is no consensus on the best surgical technique to be adopted, but unsatisfactory results can lead to an unaesthetic appearance and have negative consequences on the individual\'s selfesteem. Objective: To evaluate the aesthetics of the nasolabial appearance and the facial profile of children with complete unilateral cleft lip and palate and the fistula index based on the 2-stage palatoplasty technique with vomer flap. Method: This is a retrospective study, evaluating the nasolabial appearance during the mixed dentition age using the Asher-McDade index by three craniofacial surgeons and analyzing the fistula rate in 139 patients with complete unilateral cleft lip and palate submitted to the same surgical protocol and performed in a single center, Hospital for Rehabilitation of Craniofacial Anomalies (HRAC-USP). Kappa tests were used to assess inter- and intra-rater reproducibility. Results: 139 children were evaluated (90 boys and 49 girls). The mean age of the population during mixed dentition photography was 6.29 years. Mean Asher-McDade Index scores ranged between 2.25 and 2.4 for all parameters. Reproducibility values ranged from moderate to substantial agreement. The incidence of palatal fistula was 21.74% and the most frequent location was in the hard palate (Pittsburgh type IV), in 36.67%. Palate function was considered adequate in 79% (n=109/138) of individuals and 21% had speech impairment. Conclusion: The results of the 2-stage palatoplasty protocol seem to be favorable in the long-term follow-up, proving to be a reliable option for the treatment of patients with unilateral cleft lip and palate.